PD-1 immunology in the kidneys: a growing relationship - Chen, Ruyue; Lin, Qiang; Tang, Hanyun; Dai, Xiaomei; Jiang, Lu; Cui, Ningxun; Li, Xiaozhong (Frontiers in Immunology, 2024)
In recent years, knowledge regarding immune regulation has expanded rapidly, and major advancements have been made in immunotherapy for immune-associated disorders, particularly cancer. The programmed cell death 1 (PD-1) pathway is a cornerstone in immune regulation. It comprises PD-1 and its ligands mediating immune tolerance mechanisms and immune homeostasis. Accumulating evidence demonstrates that the PD-1 axis has a crucial immunosuppressive role in the tumor microenvironment and autoimmune diseases. PD-1 receptors and ligands on immune cells and renal parenchymal cells aid in maintaining immunological homeostasis in the kidneys. Here, we present a comprehensive review of PD-1 immunology in various kidney disorders, including renal cell carcinoma, glomerulonephritis, kidney transplantation, renal aging, and renal immune-related adverse events secondary to PD-1 immunotherapy.